The Use of History Movies to Enhance EFL Students’ Civilization Understanding The Case Study of Master One Students at The Department of English-University of Laghouat - Bouziani Lina; Djaber, Souad; Boumediene, Houda (Faculty of Letters and Foreign Languages Department of English, 2023)
Technology integration has become widely spread across a range of fields, including teaching history, to help teachers incorporate new approaches and achieve educational objectives. Therefore, the present study was conducted to evaluate technology-based instruction using historical movies as an educational tool in learning /teaching EFL history to Master 01 students at the University of Amar Thelidji, the specific objectives include introducing and exploring the effects of technology to enhance historical understanding, using historical movies to enlarge the student’s experience with history. In this study, two research instruments were used, a questionnaire with master 01 students followed by a semi structured interview addressed to 5 teachers. The study's findings support the claim that students have benefited from using historical films and are becoming more engaged in the process by demonstrating how well they work as a tool for enhancing history learning. Additionally, this tool enables learners to facilitate and reinforce their history studies as well as teachers to combine online content and activities with face-to-face instruction. Based on the findings of this study, the use of historical movies in history classes provides a starting point for further investigation into the integration of historical movies in traditional settings in order to effectively apply online content in a way that supports the teaching and learning process